Development of molecular marker for pro-vitamin A carotenoids in cassava - Gedil, Melaku A; Enok, L. (International Society for Tropical Root Crops, 2012)
Cassava is currently the third most important source of calories in the tropics and consumed as a staple food. Several cassava varieties have yellow flesh color, and contain moderate amounts of carotenoid or beta-carotene which is a precursor of vitamin A. Consumption of carotene rich foods is the most effective intervention for vitamin A deficiency. The present work is envisaged towards the genetic improvement of carotenoid content (beta-carotene) in cassava, by identifying single nucleotide polymorphism (SNP) attributed to variation in carotenoid concentration among various cassava genotypes. phytoene synthase (PSY1), b-carotene hydroxylase (HYD1), lycopene b and e cyclase (LYCB and LYCE), have been found to play a role in increasing levels of beta-carotene in plants. A total of 32 lines were drawn from the Uniform Yield Trial (UYT) stage of the cassava breeding program of IITA. The panel consists of lines with high carotenoid concentration (6ug-15ug) and low carotenoid concentration (0ug-5ug) as well as white root advanced clones. Primers for HYD1, LYCB, LYCE, and PSY1 genes designed from cassava ESTs were used to genotype the panel. Amplified PCR products were purified and sequenced. A total of 228 sequences were generated across all genes (HYD1, 49; LYCB, 62; PSY1, 59; LYCE, 58). Similarity search results of the sequences against NCBI database showed homology with pVAC genes in Ricinus communis, Zea mays, Arabidopsis thaliana, Carica papaya, and Daucus carota among others. Comparison of these sequences after multiple sequence alignment also revealed regions of conserved histidine cluster motifs that contain histidine residues: HXXX(X)H, HXX(X)HH, and HXXHH, characteristic domain of the b-carotene hydroxylase superfamily. Similarity search in Phytozome cassava (www.phytozome.net/cassava) matched full gene sequences of the carotenoid genes from which primers were designed. These primers were used to genotype a larger panel of 40 (previous 32 inclusive) carotenoid variable lines. Upon sequence analysis, a nucleotide variant was discovered in a clone with high total carotene content. Discovered nucleotide variants will be validated and ultimately converted into user friendly assay for marker-assisted breeding. This approach will contribute to enhanced genetic improvement of nutritional quality of cassava roots and provides an insight into the genetic and molecular basis of carotenoid biosynthesis.